Gas Leak Detection and Monitoring System for Enhanced Safety in Laundry Services (Borneo Engineering & Advanced Multidisciplinary International Journal, 2023)
Gas leaks are a significant hazard in the laundry service industry as they can lead to explosions, fires, and toxic gas exposure. This research project aims to develop a gas leak detection and monitoring system that utilizes MQ-2 sensors and an ESP32 controller board. The system includes a database to maintain real-time records of any gas leaks detected by the sensor using the XAMPP server platform. The sensor is placed behind the dryer machine and can detect gas leaks in the 20 cm-1000 cm range. Warning indicators such as LEDs and buzzers alert the user in case of gas leakage. Additionally, a mobile monitoring application named SIN application is developed using Kodular. The system includes a shut-off valve, which allows the user to turn off the gas source valve by switching off the red LED button in the SIN application. When the red LED on the gas leak detector is OFF, this indicates that the connected valve circuit will be closed. Therefore, this project helps laundry service operators improve the level of safety in their facilities by providing a reliable gas leak detection and monitoring system.